2017
DOI: 10.1007/s10039-017-0310-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultraschall und Stoßwelle in der Pseudarthrosentherapie

Abstract: Sinnvoll oder nicht und wann?Knochengewebe

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…( 36 ), the delay from the initial injury or the last operation was 3 to 6 months (delayed healing). Otherwise, in other papers, the Authors included those fractures that showed no progressive callus formation as well as the absence of radiographic progression of healing upon clinical examination by six months after injury ( 2 , 4 , 43 , 45 , 47 ). However, this may be due to the fact that there is no clear consensus among orthopedic surgeons in the assessment of fracture healing based on clinical evaluation and radiological examinations ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 36 ), the delay from the initial injury or the last operation was 3 to 6 months (delayed healing). Otherwise, in other papers, the Authors included those fractures that showed no progressive callus formation as well as the absence of radiographic progression of healing upon clinical examination by six months after injury ( 2 , 4 , 43 , 45 , 47 ). However, this may be due to the fact that there is no clear consensus among orthopedic surgeons in the assessment of fracture healing based on clinical evaluation and radiological examinations ( 47 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Physiological fracture healing occurs within 3 months after bone injury hrough an intricate and highly coordinated regenerative process ( 1 ). However, several local and/or systemic factors can contribute to retardation or failure of bone consolidation ( 2 ). As a result, up to 10% of patients with long bone fractures suffer from healing complications, which include both delayed and nonunion ( 1 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extracorporeal shock wave therapy (ESWT) is widely used [ 1 ] in the treatment of classic indications, including musculoskeletal disorders, e.g., plantar fasciitis [ 2 ], tendinopathies [ 3 ], and non-union fractions [ 4 , 5 ]. While interest has spread into new areas of soft tissue applications, including the field of urology, i.e., treatment of erectile dysfunctions [ 6 ], treatment sites are often directly accessible without acoustical obstruction.…”
Section: Introductionmentioning
confidence: 99%